CONSUMER ACCEPTANCE OF THE FLAVOR OF FISH FISH (Oreochromis niloticus) SMOKE BABY FLAVOR - Henry Robby Mustaqim; Syahrul Syahrul; Bustari Hasan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT The quality of baby tilapia used as raw material in processing greatly influences the smooth processing of the processing, and determines the quality of the resulting product. This study aims to determine the effect of flavor variants on smoked baby flavor tilapia on consumer acceptance and the best flavor variants as well as the total value of chemical analysis, total phenol, total acid in the processing of smoked baby flavored tilapia. The treatment factor was smoked baby tilapia with the addition of the original variant, sorbitol and salt. Organoleptic data were analyzed by ANOVA. The data that have a very significant effect are tested by the BNJ follow-up test. The results obtained from the 2 test parameters obtained the highest organoleptic (visual) value (7.68); lowest (7.48); the highest organoleptic (aroma) value (7.75); lowest (7.39); the highest organoleptic (texture) value (7.25); lowest (7.07) ); the highest organoleptic (taste) value (7.74); lowest (7.35). Then the addition of flavor variants affects the organoleptic quality of smoked baby tilapia.Keywords: nila, smoke, organoleptic